Bulky Pelvic Hodgkin Lymphoma in a Prepubertal Girl - Totadri, Sidharth; Bansal, Deepak; Bal, Amanjit; Menon, Prema (Indian Journal of Medical and Paediatric Oncology, 2017)
Pure infra-diaphragmatic presentation is rare in pediatric Hodgkin lymphoma (HL). Isolated pelvic presentation is restricted to case reports in adults. We describe a unique presentation of HL as a primary pelvic disease in an 11-year-old prepubertal girl. She was treated based on the Euronet-Paediatric Hodgkin's Lymphoma Group protocol (EuroNet-PHL-C1) recommendations and assigned to treatment Group 2 (Stage IIB). The patient had bulky disease and a suboptimal response on interim 18-fluorodeoxyglucose positron emission tomography. The child was administered chemotherapy alone. Pelvic radiotherapy was consciously avoided due to the high risk of gonadal failure. She remains disease-free for 18 months now. Treatment of pediatric HL necessitates a delicate balance between achieving cure as well as avoiding serious late effects of therapy.
Keywords: Hypogonadism; infradiaphragmatic; late effects; positron emission tomography scan; radiation